Design and synthesis of active heparan sulfate-based probes. Issue 55 (12th June 2015) - Zhou, Wen; Hsieh, Po-Hung; Xu, Yongmei; O'Leary, Timothy R.; Huang, Xuefei; Liu, Jian
Abstract : Synthesis of sulfated carbohydrate molecular probes and the utilities as specific inhibitors for carbohydrate sulfotransferases. Abstract : A chemoenzymatic approach for synthesizing heparan sulfate oligosaccharides with a reactive diazoacetyl saccharide residue is reported. The resultant oligosaccharides were demonstrated to serve as specific inhibitors for heparan sulfate sulfotransferases, offering a new set of tools to probe the structural selectivity for heparan sulfate-binding proteins.